Detection of Mandarivirus and greening bacterium using electron microscopy, PCR and RT-PCR in Kinnow mandarin nurseries in Punjab - PANT, R P; KUMAR, RAKESH; ARORA, ANITA; BARANWAL, V K (The Indian Journal of Agricultural Sciences, 2023)
Kinnow mandarin is one of the most important fruit crops in northern India particularly in Punjab. Indian citrus ringspot virus (ICRSV), Citrus yellow vein clearing virus (CYVCV) and citrus greening bacterium (CGB) are very important graft transmissible pathogens causing reduced productivity in Kinnow mandarin. A survey was undertaken in 11 kinnow mandarin nurseries, 2 to 4 star rated by National Horticultural Board in Punjab. Samples collected from these nurseries were indexed by electron microscopy, immunosorbent electron microscopy (ISEM), PCR and RT-PCR. In RT-PCR test, out of 33 samples of kinnow mandarin mother plants, 3 samples were found positive for CYVCV and 6 samples for ICRSV. In two nurseries, both the viruses were detected in the same plant indicating mixed infection in the mother plants. In ISEM test, 4 samples out of 12 samples were positive for ICRSV and 2 samples were positive for CYVCV. CGB was detected in two plants out of nine plant leaf samples collected from four nurseries. In view of these studies it is evident that molecular diagnostics as indexing tool need to be applied for the production of clean planting material of kinnow mandarin.